Switching to Doravirine/Lamivudine/Tenofovir Disoproxil Fumarate (DOR/3TC/TDF) Maintains HIV-1 Virologic Suppression Through 48 Weeks: Results of the DRIVE-SHIFT Trial - Johnson, Margaret (J Acquir Immune Defic Syndr, 2019)
BACKGROUND: Doravirine is a novel, nonnucleoside reverse transcriptase inhibitor with demonstrated efficacy in treatment-naive adults with HIV-1. METHODS: In this open-label, active-controlled, noninferiority trial, adults with HIV-1 virologically suppressed for ≥6 months on 2 nucleoside reverse transcriptase inhibitors plus a boosted protease inhibitor, boosted elvitegravir, or a non-nucleoside reverse transcriptase inhibitor were randomized (2:1) to switch to once-daily, single-tablet doravirine 100 mg with lamivudine 300 mg and tenofovir disoproxil fumarate 300 mg (DOR/3TC/TDF) or to continue their current therapy (Baseline Regimen) for 24 weeks. The primary endpoint was the proportion of participants with HIV-1 RNA <50 copies/mL (defined by the FDA Snapshot approach), with the primary comparison between DOR/3TC/TDF at week 48 and Baseline Regimen at week 24 and a secondary comparison between the groups at week 24 (noninferiority margin, −8%). RESULTS: Six hundred seventy participants (447 DOR/3TC/TDF, 223 Baseline Regimen) were treated and included in the analyses. At week 24, 93.7% on DOR/3TC/TDF vs 94.6% on Baseline Regimen had HIV-1 RNA <50 copies/mL [difference −0.9 (−4.7 to 3.0)]. At week 48, 90.8% on DOR/3TC/TDF had HIV-1 RNA <50 copies/mL, demonstrating noninferiority vs Baseline Regimen at week 24 [difference −3.8 (−7.9 to 0.3)]. In participants on ritonavir-boosted protease inhibitor at entry, mean reductions in fasting LDL-C and non-HDL-C at week 24 were significantly greater for DOR/3TC/TDF vs Baseline Regimen (P < 0.0001). Adverse events occurred in 68.9% on DOR/3TC/TDF and 52.5% on Baseline Regimen by week 24, leading to treatment discontinuation in 2.5% and 0.4%, respectively. CONCLUSIONS: Switching to once-daily DOR/3TC/TDF is a generally well-tolerated option for maintaining viral suppression in patients considering a change in therapy. REGISTRATION: ClinicalTrials.gov NCT02397096.